CHANGES OF ENZ¥MATIC ACTIVITY DURING LARVAL DEVELOPMENT OF CARP, CATLA CATLA (HAM.) - CHAKRABARTI, RINA; SHARMA, JAI GOPAL (Journal of Indian Fisheries Association, 2015)
Quantitative assays of trypsin, amylase and alkaline phosphatases were made in relation to age and food during the larval development of the Indian major carp Catla catla. The responses of all the test enzymes to age and food were identical. No enzymes were detected . from the fertilized eggs. Detectable amount of enzymes were first observed in the first day old hatchlings. All the test enzymes in the group fed normal feed tended to rise gradually with advancement of age till day 22 after which an asymptotic level was attained. Absence of food throughout the rearing period caused the enzymatic activity of the larva to remain at the lowest level throughout. When starvation was followed by feeding, enzymatic activity in the former group was consistently higher than that of latter, suggesting that feeding activity was primarily responsible in maintaining the enzymatic activity of carp larva. The enzymatic activit¥ of zooplankton was significantly higher than carp larva till d y 6 ·to 12 after which the latter exceeded the former implying that carp larva during development utilizes the exogenous enzymes of zooplankton.